Diagnostic accuracy of smear microscopy, mycobacterial culture, and GeneXpert MTB/RIF assay for diagnosis of subclinical tuberculosis: a retrospective multicenter study - Jin Shi; Yanhong Yu; Bo Li; Yuanyuan Shang; Cong Yao; Weicong Ren; Shanshan Li; Mengqiu Gao; Yu Pang (Microbiology Spectrum)
ABSTRACT Subclinical tuberculosis (TB) challenges public health interventions. This retrospective multicenter study aimed to evaluate the diagnostic efficacy of smear microscopy, mycobacterial culture, and GeneXpert MTB/RIF assay (Xpert) for subclinical TB and identify its proportion and risk factors in China. Among 560 participants diagnosed with TB, 309 (55.18%) patients had active TB, and 251 (44.82%) had subclinical TB. For subclinical TB diagnosis, smear microscopy, mycobacterial culture, and Xpert had detection rates of 11.5%, 40.6%, and 40.6%, respectively, which were significantly lower than those for active TB (25.2%, 59.2%, and 63.7% respectively). Conversely, interferon-γ release assays (IGRA) showed similar detection rates for both subclinical (85.7%) and active TB (84.1%). Age groups of 40–60 years and under 40 years, as well as employed individuals had higher risks of subclinical TB. To conclude, about 45% of TB patients were subclinical in our study. Microbiologic tests had lower diagnostic sensitivities for subclinical TB than for active TB, while IGRA positivity rates were comparable between asymptomatic and symptomatic TB patients, highlighting the potential of antigen-specific immune response in the diagnosis of these asymptomatic individuals. Further clinical trials are warranted to investigate the diagnostic flow chart in individuals with subclinical TB.IMPORTANCESubclinical tuberculosis (TB) poses a major challenge to public health interventions, especially in the wake of the COVID-19 pandemic. However, a substantial proportion of individuals have absence or non-recognized symptoms, which put great pressure on clinical diagnosis. In this study, we conducted a retrospective multicenter study to assess the performance of smear microscopy, mycobacterial culture, and GeneXpert MTB/RIF (Xpert) in diagnosis of subclinical TB. We also aimed to determine the proportion and risk factors of subclinical TB in China in order to accelerate progress towards global milestones and targets for the End TB Strategy.